THE TESTING OF TEACHER’S COMPETENCE MODEL FROM MULTIMEDIA EXPERTISE PROGRAM USING CONFIRMATORY FACTOR ANALYSIS - Muhammad Rafie Pawellangi; Hakkun Elmunsyah (Universitas Negeri Malang, 2018)
Abstract: The Testing of Teacher’s Competence Model from Multimedia Expertise Program Using Confirmatory Factor Analysis. The research aims to test the teacher’s competence model which becomes the basis of evaluating the teacher’s competence in Indonesia as well as the basis of developing the education and training to improve the competence. The tested model involves several levels of measurement construct, from competence dimension, competence group, to expertise group. The analyzed data in the research is the result of test namely Teacher’s Competence Test of Vocational High School teachers teaching Multimedia subject (N=2,744). The data is analyzed using Confirmatory Factor Analysis (CFA) approach. The analysis result shows that the tested model has satisfying model acuracy which means the model represents the actual data. The Root Mean Square Error of Approximation (RMSEA) = 0.000 (< 0.08), CFI = 1.000 (> 0.95), TLI = 1.000 (> 0.95). The findings also show that the model is able to explain the teacher’s phenomenon in the real world. Therefore, the evaluation process against the teacher’s competence and the intervention in the competence development using this model are empirically supported.